Sensitivity Test Analysis Using Reservoir Simulation on Surfactant-Polymer Injection with Core Modeling - Jannoke, Ludovika; Syaifullah, Muhammad Rizal (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This research aims to determine the results in increasing the effective recovery factor carried out by doing core modeling to be carried out for application to the field. Prior to the research, EOR screening was conducted to maximize the results, and from the EOR screening results, the EOR method that can be used is surfactant-polymer injection. This research was conducted using laboratory data from open source to do data modeling such as core data and surfactant-polymer data. After obtaining laboratory data, perform core modeling using laboratory data that is matched against laboratory test data. After the coreflooding simulation results are obtained by matching and after optimization, the next step is to up-scale the data to the field to carry out the scenario. There are three initial scenarios, namely basecase, waterflooding, and surfactant-polymer injection. After that, sensitivity tests were carried out on the total PV injection from 0.1 PV to 0.2 PV. And the maximum result was obtained in the surfactant-polymer injection scenario with 0.18 PV injected. The recovery factor was 51.21% with a total cumulative oil production of 190.3 MMBBL. Determination of the best scenario is determined through an increase in recovery factor, besides that the time carried out in all scenarios is carried out for 40 years.